Cognitive load increases risk aversion - Holger Gerhardt; Guido P. Biele; Hauke R. Heekeren; Harald Uhlig (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
We investigate how stable individuals' risk attitudes are with respect to changes in cognitive load. In a laboratory experiment using pairwise lottery choice and a within-subject design, we showthat putting subjects under load via a concurrent working-memory task significantly increases their risk aversion. Subjects made significantly faster choices under load. Regardless of load, they responded faster when choosing the less risky option in safe-risky trials, but not in risky-risky trials. We discuss how these findings relate to both dual-system and unitarysystem theories of decision making.We observe that predictions of both recent dual-system and drift-diffusion models of the decision-making process are confirmed by our data and argue for a convergence of these to-date separate strands of the literature.
Keywords: C91; D03; D81; D87; 330; risk aversion; cognitive load; working memory; dual-system approach; multiple-system approach; dual-self model; drift-diffusion model; response times